Peran Satuan Bakti Pekerja Sosial dalam Penanganan Kasus Anak Terlantar di Kota Kupang Berdasarkan Peraturan Perundang-Undangan di Indonesia - Virda Christin Tafuli; Simplexius Asa; A. Resopijani (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
Abandoned children are a type of social welfare problem where the child’s physical, mental and spiritual conditions are not met. Social workers have an important role in handling cases of abandoned children in accordance with Indonesian laws and regulations. This research aims to determine the role of the social work service unit in handling cases of abandoned children as well as the challenges and obstacles faced in handling cases of abandoned children. This research uses empirical research methods that are empirical juridical in nature. The sample was selected by purposive sampling, data collection techniques used interviews, observation and documentation review. Social workers strive to rescue children from dangerous environments, help provide temporary shelter if necessary, and collaborate with various parties to ensure the safety and welfare of children, in providing protection for abandoned children social workers identify children who are at risk of experiencing neglect, exploitation or violence, this is done through surveys, direct interactions, or reports from other parties, after identifying children at risk, social workers carry out an in-depth evaluation of their situation by conducting an assessment. The results of the research on the role of social workers in handling abandoned children, namely companions as facilitators and counselors, as service providers or liaisons and advocates, however there are several obstacles and challenges faced, namely unclear identity of children, complex conditions of children’s families, long legal processes, limited resources and lack of public awareness.